Housewives and Virtual Market Shop during the Coronavirus Pandemic: Insight from Women's Empowerment Process - Muslim, Aziz (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
Covid-19 pandemic, the coronavirus disease, has negatively impacted the economy, especially for underprivileged individuals and informal sector workers that lost their jobs due to strict government policies. Consequently, they have encountered difficulties in making ends meet for their families. This research aims to describe the efforts made by housewives and their impact on supporting life needs during the Covid-19 pandemic. To respond to this question, the analysis uses a qualitative method with a case study approach. So that, this study shows that the several efforts do homemakers for building virtual markets, optimizing skills, and creating businesses for cooperating parties. It is for the income problem of insufficient capital and avoids a loss. Moreover, those efforts have an impact on creating self-employment opportunities and on the sustainability of family income.